Contribution of Micronutrient Fertilization in Wheat Production and its Economic Repercussions: Micronutrient Fertilization in Wheat - Raheem, Majid; Chaudhary, Ehsan-ul-Haq; Khalid, Rizwan; Chaudhary, Muhammad Akram; Timmer, Vincent (Biological Sciences - PJSIR, 2010)
Wheat response to the application of Zn, Fe and B in rice-wheat cropping pattern at ten locations in the fields in the Punjab, Pakistan was studied. The highest mean wheat grain yield (4707 kg/ha) was recorded with application of Zn:B @ 5:1 kg/ha, followed by 4678 kg/ha with Zn:Fe @ 5:10 kg/ha. The three micronutrients increased the grain yield from 1.8 to 11.8% over control, highest being recorded with the application of Zn:B @ 5:1 kg/ha. Combined application of all the three micronutrients reduced the grain yield by 1% compared to the highest yield attained by the combine application of Zn and B. However, the application of Zn @ 5 kg/ha proved to be the most economical micronutrient application with VCR of 4.80. None of the three nutrients increased the wheat grain yield in Gujrat, whereas Zn significantly increased the grain yield over control in Mandi Bahauddin. Straw to grain ratio of wheat was significantly decreased by the application of micronutrients over control mainly due to increase in grain weight.